Correction to: Health literacy in indigenous people with chronic disease living in remote Australia - Haunnah Rheault; Fiona Coyer; Lee Jones; Ann Bonner (BMC, 2019)
In the original publication of this article [1], some values are missing in Table 3. Table 3 is revised in the updated figure below: